Development of a research-based science learning curriculum of science classroom project management in the northeast - Bongboot, Dechathon (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2025)
The objectives of this research were 1) the development of a research-based local science learning curriculum for enrichment projects in science, mathematics, technology, and environment (SMTE), 2) the study of the effectiveness of the development of a research-based local science learning curriculum for enrichment projects in science, mathematics, technology, and environment (SMTE), and 3) evaluating the effectiveness or quality of local science curricula using research as the basis for special science, mathematics, technology, and environment classroom projects. in the northeast. The research was conducted in 4 steps: Step 1, the study of basic information, Step 2, curriculum development, Step 3, curriculum trial, and Step 4, evaluation and improvement of the curriculum. The samples were Mathayomsuksa 6/11 students at Bung Ken School, Bueng Kan Province, and the second semester of the academic year 2023, consisted of 34 students. The research instruments were 1) Questionnaire on the current and desired conditions of the development of local science curricula using research as a base. 2) Lesson management plan for the learning unit on biological research on the nature of living things and biological diversity. Biology in the Lok Kut Thing Wetland, Bueng Kan Province. 3) A research-based local science learning curriculum of enrichment project of Science, Mathematics, Technology, and Environment (SMTE) 4) Performance assessment and learning, and 5) curricular satisfaction. The statistics used in the data analysis were mean, standard deviation, percentage, and t-test. The results of the research found that: 1) Developing a local science curriculum using research as the basis of a special science, mathematics, technology, and environment classroom project in the developed northeastern region. Consists of 1) Local curriculum analysis table 2) Introduction 3) Vision 4) Mission 5) Objectives 6) Important student competencies 7) Desired characteristics 8) Local curriculum framework/local learning content 9) Focus points Context, needs of the educational institution 10 ) Structure of the curriculum 11) Content 12) Course description 13) Learning management plan Including 5 units were (1) knowledge about biodiversity and the origin of life (2) Biodiversity Research in Kut Ting Wetlands (3) Studying biodiversity in the world’s wetlands (4) Classification, and morphology of biodiversity in the Kut Ting World Wetlands (5) Biodiversity Research Report in Kut Ting World Wetlands. The amount of the learning period is 20 hours. Research-Based Evaluation of the Effectiveness of Local Science Curriculum. Based on the results of data analysis. Including 1) Learning achievement after the experiment was significantly higher than before the experiment at the 0.05 level (t-test เท่ากับ 16.58*). 2) Overall student performance and learning behavior are at the highest level, and 3) Students were satisfied with the course at the highest level.